The Application of Thermal Solar Energy to High Temperature Processes: Case Study of the Synthesis of Alumina from Boehmite. (9th January 2014) - Padilla, Isabel; López-Delgado, Aurora; López-Andrés, Sol; Álvarez, Marta; Galindo, Roberto; Vazquez-Vaamonde, Alfonso J.
Abstract : The aim of this paper is to evaluate the feasibility of obtaining alumina from boehmite using a free, clean, and unlimited power source as the solar energy. Boehmite was obtained by hydrothermal treatment of a hazardous waste coming from aluminum slag milling. The waste is considered as a hazardous substance because of it releasing toxic gases (hydrogen, ammonia, methane, and hydrogen sulfide) in the presence of water. The as-obtained boehmite was transformed into alumina, in air atmosphere, using a solar energy concentrator (Fresnel lens). The solar installation provides a power density of 260 W·cm −2 which allows reaching temperatures upper than 1000°C at few minutes of exposure. Tests were performed at different periods of time that ranged between 5 and 90 min. The percentage of transformation of boehmite into alumina was followed by the water content of samples after solar radiation exposure. Samples were characterized by X-ray diffraction, infrared spectroscopy, and thermogravimetry. Metastable aluminas started to appear at 5 min and the crystalline and stable phase corundum at 10 min of solar radiation exposure.